Sudden cardiac death in Hispanic Americans and African Americans. - Gillum, R F (1997)
OBJECTIVES: The goal of this study was to estimate rates of sudden cardiac death in US Hispanics and African Americans. METHODS: Data on coronary deaths occurring outside of the hospital or in emergency rooms were examined for 1992. RESULTS: In 1992, 53% (8194) of coronary heart disease deaths among Hispanic Americans 25 years of age and older occurred outside of the hospital or in emergency rooms. The percentage was lower among Hispanics than among non-Hispanic Whites and Blacks. Age-adjusted rates per 100,000 were lower in Hispanics than in non-Hispanic Whites or Blacks (Hispanic men, 75; White men, 166; Black men, 209; Hispanic women, 35; White women, 74; Black women, 108). The percentages dying outside of the hospital or in emergency rooms were higher in young persons, those living in nonurban areas, and those who were single. CONCLUSIONS: The percentage and rate of coronary deaths occurring outside of the hospital or in emergency rooms were lower in Hispanics than in non-Hispanics; African Americans had the highest rates. Further research is needed on sudden coronary death in Hispanic Americans and African Americans.